Analisis Pencapaian Realisasi Pajak dan Retribusi Daerah Serta Dampaknya Terhadap Pendapatan Asli Daerah - Rahman, Rahman Pura (Insan Cita Bongaya Research Journal, 2021)
The implications of regional autonomy require local governments to manage regional finances to increase regional independence so that dependence on the central government decreases. To increase regional financial independence, one of the important indicators to be managed is local revenue. Regional taxes and levies are the main source of local revenue. This study aims to analyze the realization of regional taxes and levies and their impact on local revenue. The study was conducted in 24 district/city governments throughout the province of South Sulawesi. Data were collected using documentation techniques in the form of budget realization reports. The data was observed for two years, namely in 2017 and 2018. So that the number of data observed was 48 budget realization reports. Data analysis using multiple regression analysis techniques. The results of the study show that in general, district/city governments throughout the province of South Sulawesi have achieved the target for local tax revenues, while for regional retribution revenues, in general, they have not achieved it. Local taxes have a significant positive effect on local revenue. And regional levies have a significant positive effect on regional revenue.